Lodgepole pine (Pinus contorta Douglas ex Loudon) invasion in subarctic Iceland: evidence from a long-term study - Pawel Wasowicz; Guðrún Óskarsdóttir; Þóra Ellen Þórhallsdóttir (NeoBiota)
The North American lodgepole pine (Pinus contorta) has been widely introduced globally and is now considered invasive in several countries. It was first planted in subarctic Iceland in the 1950s. Recently, the forestry sector has strongly promoted it as an attractive means of carbon capture to mitigate global climate change. It is now the most extensively planted tree species in Iceland. We describe the expansion of the lodgepole pine from a mid-20th-century plantation in Steinadalur, southeast Iceland, and decadal changes between 2010 and 2021. The extent of occurrence expanded nearly tenfold, with tree number and population density reflecting exponential growth patterns. The lodgepole pine colonised diverse habitats, including native birch woodlands and heathland, and was associated with significant reductions in vascular plant species richness and diversity. We conclude that lodgepole pine has the characteristics of an invasive species in Steinadalur and that this will also apply to many native ecosystems across most lowland regions of Iceland. Our study highlights the urgent need for management strategies to mitigate the long-term ecological impacts of lodgepole pine invasion in subarctic environments.